Grafting of Cellulose Extracted from Kenaf Using Xanthate Method - Sherif M.A.S. Keshk (Journal of Basic & Applied Sciences, 2014)
Mass spectra of reconstructed ion chromatogram (MRIC) technique are used to follow up the grafting copolymerization of 1-vinyl-2-pyrrolidinone (VP), 1-vinyl-3-anisylidine-2-pyrrolidinone (VAP) and ethylmethacrylate (EMA) and cellulose extracted from kenaf using xanthate method. Grafting is carried out under ionic and/or free radical mechanism conditions. Factors affecting grafting yield such as temperature, sodium hydroxide concentration, liquor ratio, carbon disulfide concentration, monomer and grafting time have been studied.